Effects of comparative advantage on exports: A case study of Iranian industrial subsectors - Nonejad, Masoud (Journal of Economics and Behavioral Studies, 2013)
One of the informational requirements in planning import and export activities is to an awareness of a country’s comparative advantage in the production of goods and services. The present paper attempts to assess Iran’s Revealed Comparative Advantage (RCA) in industrial subsectors based on two-digit code of the International Standard Industrial Classification (ISIC) and effects of five top subsectors with the highest average of RCA on the total Iranian real industrial exports. RCAs for Iranian industrial subsectors (during 2001-2010) were calculated for 2001-2010 time period and seasonal data (2001- 2010) were collected to estimate the RCA Model. Auto Regressive Distributed Lags (ARDL) Method was employed to investigate the effects of these subsectors on the total Iranian real industrial exports. The econometric results show that the subsectors with highest RCA average have a positive and significant effect on the total Iranian real industrial exports.